Intravascular Ultrasound Imaging–Guided Versus Coronary Angiography–Guided Percutaneous Coronary Intervention: A Systematic Review and Meta‐Analysis. Issue 5 (3rd March 2020) - Darmoch, Fahed; Alraies, M. Chadi; Al‐Khadra, Yasser; Moussa Pacha, Homam; Pinto, Duane S.; Osborn, Eric A.
Abstract : Background: Intravascular ultrasound (IVUS) guidance during percutaneous coronary intervention (PCI) offers tomographic images of the coronary vessels, allowing optimization of stent implantation at the time of PCI. However, the long‐term beneficial effect of IVUS over PCI guided by coronary angiography (CA) alone remains under question. We sought to investigate the outcomes of IVUS‐guided compared with CA‐guided PCI. Methods and Results: We performed a comprehensive search of PubMed, Medline, and Cochrane Central Register, looking for randomized controlled trials and observational studies that compared PCI outcomes of IVUS with CA. Data were aggregated for the primary outcome measure using the random‐effects model as pooled risk ratio (RR). The primary outcomes were the rate of cardiovascular death, need for target lesion revascularization, occurrence of myocardial infarction, and rate of stent thrombosis. A total of 19 studies met the inclusion criteria, comprising 27 610 patients divided into IVUS (n=11 513) and CA (n=16 097). Compared with standard CA‐guided PCI, we found that the risks of cardiovascular death (RR, 0.63; 95% CI, 0.54–0.73), myocardial infarction (RR, 0.71; 95% CI, 0.58–0.86), target lesion revascularization (RR, 0.81; 95% CI, 0.70–0.94), and stent thrombosis (RR, 0.57; 95% CI, 0.41–0.79) were all significantly lower using IVUS guidance. Conclusions: Compared with standard CA‐guided PCI, the use of IVUS imaging guidance to optimize stent implantation is associated with a reduced risk of cardiovascular death and major adverse events, such as myocardial infarction, target lesion revascularization, and stent thrombosis.